Lecturers’ Strategies to Enhance Students’ Motivation in Learning Arabic at UINSI Samarinda - Mubarak, Ahmad; Ardiansyah, Ardiansyah; Allam, Naufal; Santoso, Rahmad Adi; Zaki, Muhammad; Abdullah, Muhammad Rama (Borneo Journal of Language and Education, 2023)
In Indonesia, Arabic language instruction at higher education institutions frequently faces significant challenges: low student motivation leads to passive participation, delayed vocabulary acquisition, and limited communicative competence, despite the crucial role of Arabic in academic and religious contexts. This phenomenon poses challenges to the quality of Arabic language education and the effectiveness of knowledge transfer within Islamic universities. This study aims to explore lecturers’ strategies to enhance students’ intrinsic motivation in learning Arabic at UINSI Samarinda. A qualitative case study approach was employed, involving five lecturers and fifteen students selected through purposive sampling. Data were collected via semi-structured interviews, participatory observation, and instructional material documentation, then analyzed using the Miles & Huberman interactive model, including data reduction, display, and verification through member checking. The findings identified three main lecturer strategies: (1) interactive pedagogy, fostering active participation and communicative mastery; (2) cultural and religious contextualization, reinforcing material relevance and students’ emotional engagement; and (3) the use of media and technology, supporting autonomy and self-directed learning. The integration of these strategies establishes a sustainable motivation pattern that significantly enhances student engagement. This study reinforces the Self-Determination Theory framework, demonstrating that fulfilling the needs for autonomy, competence, and relatedness is essential for foreign language learning motivation. Practical implications highlight the necessity of holistic teaching strategies and curriculum content aligned with students’ experiences and values. Future research is recommended to examine the long-term impact of these strategies on Arabic language proficiency and the sustainability of learning motivation.